2010
DOI: 10.3126/ijls.v4i0.3496
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile of Tracheal Aspirates of the Patients Attending Neuro-hospital Nepal

Abstract: The tracheostomized patients are colonized mostly by gram negative bacteria which lead to either tracheobronchitis or bronchopneumonia. This study was conducted to isolate and identify the potential pathogen causing post tracheostomy infection. A cross-sectional study was conducted during April 2008 to February 2009 based at Neuro Center, Kathmandu. Tracheal aspirates of 50 patients having fever more than 38°C were collected and analyzed for bacterial content. Out of the 50 cases, 45(90%) cases showed bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
3
3
1
Order By: Relevance
“…Multi-drug resistant P. aeruginosa (MDRPA) strains are the most challenging organisms for the clinicians to be overcome. In our study 89.4% of the total isolates from the clinical samples were MDRPA which is similar to a study carried out in Nepal (Koirala et al 2010. In a recent study carried out in a tertiary care hospital in Nepal (Karki et al 2011), MDRPA were also isolated from the clinical samples.…”
Section: Resultssupporting
confidence: 90%
“…Multi-drug resistant P. aeruginosa (MDRPA) strains are the most challenging organisms for the clinicians to be overcome. In our study 89.4% of the total isolates from the clinical samples were MDRPA which is similar to a study carried out in Nepal (Koirala et al 2010. In a recent study carried out in a tertiary care hospital in Nepal (Karki et al 2011), MDRPA were also isolated from the clinical samples.…”
Section: Resultssupporting
confidence: 90%
“…In this study high growth rate was found from different clinical samples, and similar results have been reported in the previous study carried out at the same hospital [ 15 , 16 ]. Most predominant pathogens in this study were Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the study showed high growth rate, which was in accordance with the previous study, which reported culture positivity of 90% [13]. Polymicrobial growth was observed in one-tenth of the cases and the growth of multiple organisms from tracheal specimen has been mentioned in similar studies [14, 15].…”
Section: Discussionsupporting
confidence: 89%